(untitled) (Journal of Universal Science Research, 2025)
Trichoscopy is a non-invasive visual and microscopic examination method performed using a specialized optical device (trichoscope) to assess the scalp and hair. It is widely used in dermatology and trichology to identify the causes and stages of hair loss, including alopecia. This study aims to evaluate the diagnostic, clinical, and prognostic significance of trichoscopy in the early and accurate diagnosis of alopecia and to assess its effectiveness in clinical practice.